DNA-mediated cell surface engineering for multiplexed glycan profiling using MALDI-TOF mass spectrometry. Issue 8 (18th May 2016) - He, Ziyi; Chen, Qiushui; Chen, Fengming; Zhang, Jie; Li, Haifang; Lin, Jin-Ming
Abstract : A MALDI-TOF MS based approach is developed for multiplexed profiling of cell surface glycans using a DNA-mediated cell surface engineering strategy. Abstract : Glycans are crucial for many key biological processes and their alterations are often a hallmark of disease. Thus, multiplexed and sensitive analysis of glycans is of intense interest. Here we report a novel approach using DNA-mediated cell surface engineering for glycan profiling by MALDI-TOF mass spectrometry (MS). Following lectin binding, DNA amplification and hybridization, glycans on the cell surface are specifically labeled by short DNA probes, which can be facilely released, ionized and detected in MALDI-TOF MS. This strategy converts the analysis of glycans to the detection of DNA probes, overcoming the complicated composition and low ionization efficiency of glycans, enabling in situ detection and facilitating multiplex analysis. The amplification procedure also improves the sensitivity. This approach has been applied to evaluate glycomic alterations in cancer cells and provided the intrinsic distribution of glycans in tissues using MALDI imaging mass spectrometry.